Mechanics of fluids - Potter, Merle C.; Wiggert, D. C.; Ramadan, Bassem H.; Shih, Tom I-P; Chhabra, Raj (Cengage Learning, 2017)
Gain an understanding of fluid mechanics and the ability to analyze this important phenomena encountered by practicing engineers with MECHANICS OF FLUIDS, 5E. The authors use proven learning tools to help you visualize many difficult-to-understand aspects of fluid mechanics. The mathematics used in derivations are readily accessible to you as an undergraduate engineering student. This edition's accompanying Multimedia Fluid Mechanics DVD-ROM helps you gain insights and develop intuition about fluid flow as you view mathematical relationships through movies and conduct actual simulations. The book's companion website includes mini-exams and solutions as well as video tutorials to assist you in further mastering fluid mechanics as an emerging professional.